Anaerobic Propane Oxidation for Biological Sulphateand Thiosulphate Reductions - Diansyah, Gusti (Maspari Journal : Marine Science Research, 2014)
The existence of microbial populations that use short chain alkanes (SCA) (ethane, propane and butane) as potential electron donors for the reduction of sulphate has been recently reported. The useof sulphur compounds in many chemical processing leads wastewaters containing high concentration of sulphate and thiosulphate. Batch experiments were studied to determine the ability of mixed sediment cultures from Aarhus and Eckernförde Bay to anaerobically reduce sulphate and thiosulphate coupled to propane as electron donor. In the presence of propane, sulphide production from all sulphate and thiosulphate bottles was higher than the sulphide production when the propane was not added.